New species and new records of the hygropetric water beetle genus Oocyclus Sharp from South America (Coleoptera: Hydrophilidae) - Short, Andrew Edward Z.; Greene, Luke; Garcia, Mauricio (Zootaxa, 2013)
Three new species of Oocyclus Sharp, 1882 are described from tropical South America: O. maluz sp. n. (Venezuela), O. miza sp. n. (Venezuela), and O. brunneus sp. n. (Bolivia). New distributional records are provided for O. andinus Short & García, O. coromoto Short & García (newly recorded from Suriname), O. floccus Short & García (newly recorded from Guyana and Suriname), O. iguazu (Oliva), O. meridensis Short & García, O. petra Short & García (newly recorded from Guyana and Suriname), O. trio Short & Kadosoe (newly recorded from Guyana), O. trujillo Short & García, and O. yubai Clarkson & Short (newly recorded from Paraguay). Updates to the keys of the Brazilian and Venezuelan Oocyclus species are provided.